Admissibility of craniofacial superimposition evidence as a means of forensic identification in Malaysia / Amar Singh Ishar Singh - Amar Singh, Ishar Singh (2005)
Craniofacial superimposition is a method of comparing the characteristic features of a skull with a photograph of a person whose identity is known. As a technique to aid the personal identification of unknown human remains, it is not new, and its application can be traced back to the late 19th Century. It can be used not only in the identification of the dead but also the living and is fast becoming an important method in forensic anthropology. This is because surveillance cameras are often employed as silent witnesses in crime scenes such as at banks, convenience stores and airports. This research will outline the developments in the field of craniofacial superimposition, from the earliest method of using viewing boxes, slide projector and overhead projector, to that of video technology and now to the incorporation of e- technology. The eight cases of superimposition conducted by the Malaysian police authorities, of which three have reached the courts of law, will be discussed in depth. This will show the practical aspects of facial superimposition which could be a guide for enforcement officers in their pursuit for justice. The legal implications of such evidence are also discussed. The question of relevancy and admissibility of the opinion evidence of the craniofacial superimposition expert has been an issue in the courts and this research will delve into its merits. Creating an awareness on the legal and scientific validity of this field of identification will ensure that more such applications are accepted by the Malaysian courts.